The training of the Chemistry teacher for inclusive education (Research, Society and Development, 2023)
The article aims to describe the development of two extension projects with students from technical and undergraduate courses and teachers from the Federal Institute of Education, Science and Technology of RO – Campus Ji-Paraná related to aspects and challenges of special education in an inclusive perspective. The methodology adopted promoted pedagogical workshops aimed at the two audiences involved (teachers and students) and the promotion of the event I Symposium on Inclusion and Diversity GPDIN: discussing knowledge for Inclusive Education from the perspective of ethnic-racial relations, people with disabilities and sexual diversity  in partnership with the Center for Assistance to People with Specific Needs (NAPNE) and the research group GPDIN. Among the results, the interest of students in understanding about inclusion, the possibilities of working with the target-public students from Special Education-EPAEE, and the need for educational institutions to establish partnerships with society, demystifying erroneous ideas about the schooling of students with disabilities.